ANALYSIS OF THE EFFECT OF THE CASHIER CLOSING SYSTEM ON THE ACCURACY OF CASH BILLING CROSCHECK AT JIH HOSPITAL, YOGYAKARTA - Kristin Kristin; Nurfauziah Nurfauziah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates the influence of the cashier system closing process on the accuracy of cash billing cross-checks at PT Unisia Medika Farma (RS JIH) in Yogyakarta. Employing a mixed-methods approach, the study combines quantitative analysis of cash billing records from July, August, and December 2024 with qualitative insights from in-depth interviews with accounting staff. The findings reveal persistent inaccuracies in recording journal dates, with error rates ranging from 7.70% to 8.40% across the three months, indicating a systemic issue within the closing procedures. Qualitative analysis identified four main themes: human error as the primary constraining factor, established policies and procedures that face implementation gaps, significant impacts on financial stability including receivables backlogs and disrupted cash flow, and potential strategies for improvement. These strategies include implementing continuous training programs, stricter monitoring of outstanding receivables, enhancing inter-unit communication, and exploring automation technologies. The research contributes practically by providing data-driven recommendations for strengthening financial controls at RS JIH, and theoretically by extending the study of cashier system accuracy into the complex healthcare environment. The study concludes that improving the cashier system closing process is essential for enhancing financial reporting accuracy, strengthening internal controls, and ultimately supporting the hospital's capacity to deliver quality patient care through sound financial management.